Development of loan players in professional football - Niklas Günter; Lars Vischer (Universität Münster, Institut für Organisationsökonomik, 2024)
This study analyses the development of loan players in the German Bundesliga from 2010/2011 to 2021/2022, motivated by the increasing importance of player loans in professional football and upcoming FIFA rule changes to reduce loans. The study analyses 378 loan transfers and compares them with 6,162 non-loan players. The focus is on the three main protagonist: the loaned player, the lending club and the loaning club. It is found that loan players do not receive more playing minutes than average Bundesliga players and that there is no recognisable increase in market value for the loaning club, which does not improve the negotiating position when selling players. In our data, the loaning club also does not benefit significantly from the sporting performances of the loaned players. – – Diese Studie untersucht die Entwicklung von Leihspielern in der deutschen Bundesliga von 2010/2011 bis 2021/2022, motiviert durch die steigende Bedeutung der Spielerleihen im Profifußball und bevorstehende FIFA-Regeländerungen zur Reduktion von Leihen. Analysiert werden 378 Leihtransfers und mit 6.162 Nicht-Leihspielern verglichen. Der Fokus liegt auf den drei Hauptakteuren: dem verliehenen Spieler, dem verleihenden und dem ausleihenden Verein. Es zeigt sich, dass Leihspieler nicht mehr Spielminuten erhalten als durchschnittliche Bundesligaspieler und keine Marktwertsteigerung für den verleihenden Verein erkennbar ist, was die Verhandlungsposition beim Spielerverkauf nicht verbessert. Der ausleihende Verein profitiert in unseren Daten ebenfalls nicht signifikant von den sportlichen Leistungen der Leihspieler.
Keywords: J41; L83; M55; Z20; Z21; Z22; 650; Bundesliga; Development; Football; Loan Player; Market Value